STUDENT TEACHING MATERIALS AND SCIENCE LITERATURE IN SCIENCE LEARNING DURING THE COVID-19 PANDEMIC - Eka Puspita Rahayu; Indarini Dwi Pursitasari; Surti Kurniasih (JPPS (Jurnal Penelitian Pendidikan Sains), 2021)
The research aims to analyze the teaching materials needed by the teacher and the level of students' scientific literacy in the science learning process in the COVID-19 pandemic era. The descriptive quantitative method was utilized in the present study. The subject of the survey is 35 science teachers in Bogor and 150 grade VIII students at one of the junior high schools in the Bogor district. The instruments used in this study were questionnaires and scientific literacy tests. The collected data were analyzed quantitatively by calculating the percentage acquisition of students' scientific literacy then categorized. The study results revealed that the teaching materials used were not proportional in containing aspects of scientific literacy; 50% of students have scientific literacy ability in the low category, 40% in the moderate category, and 10% in the high category. The questionnaire results indicate that the factors affecting students' scientific literacy are their interest in science, learning motivation, teacher strategies in learning, and the facilities.